Comparative Analysis of the Emotional Intelligence Development of Adolescents with Different Levels of Psychological Competence - Frolova, Olga; Kashkaryova, Lyudmila; Serbova, Olga; Malykhina, Tatiana (Journal of History Culture and Art Research, 2019)
Within the proposed article, the focus is on the development of the emotional intelligence of adolescents and the impact of their psychological competence on them. The authors state that the developed emotional intelligence provides a person with a good understanding and managing of his/her emotions and a compassionate attitude and flexible response to the emotional manifestations of people nearby. People with high emotional intelligence have developed self-awareness, self-control, social understanding and are able to manage relationships with other people. Generalization of the most famous scientific approaches to the study of emotional intelligence allowed to dwell on the model of emotional intelligence which in content and structure represents a set of such abilities: perception and identification of emotions; managing emotions and feelings, both of oneself and of others; understanding of emotions; facilitation of thinking. Human emotional intelligence is formed during his/her life. Adolescence is the most sensitive to the development of emotional intelligence, because it is at this age period that intellectualization of all mental processes occurs, when "emotions can become intelligent" and "intelligence can become emotional" due to the coordinated interaction of the right and left hemispheres of the brain. Emotionality plays an important role in the development of emotional intelligence. In adolescence, on the one hand, there is a complication and instability of the emotional sphere of personality, intensification of emotions and feelings, their intensity and diversity; and, on the other hand, the ability to self-regulate, the ability to slow them down with the help of willpower, are emerging and developing. This enables the teenager to consciously construct his / her self-concept, his / her own value system, personal outlook and develop his / her emotional intelligence. These data were confirmed by the experimental study, which was carried out by comparing two groups of adolescents: the Lyceum students – a close-knit student group and members of the circle of "Psychological Studies", who were able to increase the level of psychological competence through self-discovery and development of emotional sphere. The adolescents – members of the circle showed higher rates of most components’ development of emotional intelligence than the adolescents – students of Berdiansk Lyceum, who hadn’t had this training. Thus, we are convinced that the emotional intelligence of adolescents can be developed under the condition of purposeful psycho-corrective influence, with the use of interactive methods.